Kemampuan Menulis Artikel Ilmiah Populer Siswa Kelas VIII A SMP Angkasa Kupang Tahun Pelajaran 2025/2026 - Alex Missael Adu; Richard Oematan; Sanhedri Boimau (KAMPUS AKADEMIK PUBLISING, 2026)
The problem in this study is how the ability to write popular scientific articles in eighth-grade students of SMP Angkasa Kupang. The purpose of this study is to describe the ability of eighth-grade students of SMP Angkasa Kupang in writing popular scientific articles. The method used in this study is qualitative description to facilitate the researcher in conducting in-depth and systematic data analysis to provide an accurate picture of the facts in the field. The results of the study show that the ability to write popular scientific articles in the introduction aspect is in the fairly good category with an average score of 73.5. Most students have been able to write a good introduction, although there are still deficiencies in developing the background and purpose of writing systematically. The writing ability in the content aspect is also in the fairly good category with an average score of 73.5. Students have generally been able to express ideas and opinions, but there are still weaknesses in idea development, depth of analysis, and coherence between paragraphs. The writing ability in the conclusion aspect shows relatively similar results with an average score of 73.5. Most students have been able to formulate conclusions and suggestions, but some have not been able to formulate a proper and comprehensive conclusion. Overall, the ability to write popular scientific articles of eighth-grade students of SMP Angkasa Kupang is in the fairly good category with a class average score of 73. The classical learning mastery level reached 76.47%, with 13 students declared proficient and 4 students not yet proficient, with a classical failure rate of 23.53%. The results of the study indicate that students have basic abilities in writing popular scientific articles, but improvement is still needed, especially in the aspects of logical, systematic, and communicative thinking in composing written works.